Selected Papers from the ICEUBI2019 - International Congress on Engineering - Engineering for Evolution - Calado, Maria do Rosário Alves; Silva, Jorge Miguel dos Reis (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Energies SI Book "Selected Papers from the ICEUBI2019 - International Congress on Engineering - Engineering for Evolution", groups six papers into fundamental engineering areas: Aeronautics and Astronautics, and Electrotechnical and Mechanical Engineering. ICEUBI-International Congress on Engineering is organized every two years by the Engineering Faculty of Beira Interior University, Portugal, promoting engineering in society through contact among researchers and practitioners from different fields of engineering, and thus encouraging the dissemination of engineering research, innovation, and development. All selected papers are interrelated with energy topics (fundamentals, sources, exploration, conversion, and policies), and provide relevant data for academics, research-focused practitioners, and policy makers.